Honest Engine - Dargan, Kyle G. (Book collections on Project MUSE., 2015)
In this his fourth collection, award-winning poet Kyle Dargan examines the mechanics of the heart and mind as they are weathered by loss. Following a spate of deaths among family and friends, Dargan chooses to present not color-negative elegies but self-portraits that capture what of these departed figures remains within him. Amid this processing of mortality, it becomes clear that he has arrived at a turning point as a writer and a man. As the title suggests, Dargan aspires toward an unflinching honesty. These poems do not purport to possess life's answers or seek to employ language to mask.